2013
DOI: 10.1212/wnl.0b013e318281550e
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder taping reduces injury and pain in stroke patients

Abstract: This study provided Class III evidence that tri-pull shoulder taping was ineffective in significantly reducing shoulder pain in patients with acute stoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 12 publications
1
53
0
Order By: Relevance
“…There are a few RCTs with mixed results on shoulder strapping for the prevention of shoulder pain after acute stroke. [121][122][123] Each study used different strapping (or taping) techniques and measured different pain outcomes. In the largest of these, Pandian and others 123 randomized 162 patients with acute stroke to either shoulder taping or sham taping.…”
Section: Assessment Prevention and Treatment Of Hemiplegic Shouldermentioning
confidence: 99%
“…There are a few RCTs with mixed results on shoulder strapping for the prevention of shoulder pain after acute stroke. [121][122][123] Each study used different strapping (or taping) techniques and measured different pain outcomes. In the largest of these, Pandian and others 123 randomized 162 patients with acute stroke to either shoulder taping or sham taping.…”
Section: Assessment Prevention and Treatment Of Hemiplegic Shouldermentioning
confidence: 99%
“…Several studies have suggested positive effects of taping on shoulder pain (46)(47)(48). One study and 1 review reported insufficient findings (49,50). Our study found that the SPADI of stroke patients with HSP can be reduced after 3 weeks of KT intervention.…”
Section: Acknowledgementmentioning
confidence: 48%
“…There are two additional reviews suggesting that the onset of the shoulder pain could be delayed by this technique (Ada, Foongchomcheay, & Canning, 2005;Smith, 2012). The most recent RCT performed by Pandian et al (2013) is the largest study to date. This study randomized 162 first-ever patients with stroke within 48 hours of stroke onset to receive shoulder taping versus sham taping for 2 weeks.…”
Section: Strapping and Sling (Supportive Device)mentioning
confidence: 99%